Opposition, association, and reformism: the collective action of physicians in Colombia (1990-2015) - Mauricio Lenis Gómez (Revista Colombiana de Sociología, 2017)
The paper analyzes the changes in the exercise of the medical profession and in the labor conditions of physicians as a result of a series of social (in the work environment), scientific (in the profession), and legal (structural reforms of the healthcare system and labor regulation) transformations, as well as the main collective actions carried out between 1990 and 2015 by a large number of physicians in Colombia in order to face those changes. Two theoretical perspectives were used: first, a focus on work culture that considers the relation between work and culture as a process in which agents update their culture in specific power contexts and relations, amidst conflict and bargaining processes that mark the interactions of subjects. Second, the theory of collective action and its focus on political struggle, understood as the public and collective interaction among different actors, in a conflicting relationship where the Government is one of the parties. The results of the struggle affect the interests of one of the parties, depending on which claims end up prevailing. Three types of collective actions were carried out by physicians: social protests to oppose healthcare reforms and claim their labor rights; association aimed at achieving the unification of the medical profession and having a single interlocutor with the Government; and the use of the law in order to promote changes in the regulation of the health system and the practice of medicine. Through their collective actions, part of the medical sector consolidated itself as an emerging political actor that not only fought for its interests, but also participated as a key protagonist in shaping the field of health in Colombia, in the context of the reforms to the health system. Likewise, those actions made it possible for physicians to resist, shape, or filter the effects of the changes to their work culture.